Composición química de placentas de dos grupos poblacionales - Julca V., Rudy (1999)
Placental contents of humidity, lipids, ashes, carbohydrates, DNA, RNA and proteins were observed in samples obtained immediately after normal delivery from two groups of pregnant women one in "Maternidad Municipal de Chorrillos" and other in a private Hospital in San Isidro.Selected subjects did not show any pathological condition: their ages varied from 20 to 35 years and had no more than two previous deliveries.It was found a significant difference between the means of lipid content, the first group having lower level that the second. The rest of components observed, including weight of placenta, newborn weigh, length and gestatinal age did not show any significant differences. lt can be assumed that 2(2) 103-110 (1999)both groups had similar nutritional levels during pregnancy.